2014
DOI: 10.1007/s00605-014-0703-6
|View full text |Cite
|
Sign up to set email alerts
|

Lineability of non-differentiable Pettis primitives

Abstract: Abstract. Let X be an infinite-dimensional Banach space. In 1995, settling a long outstanding problem of Pettis, Dilworth and Girardi constructed an X-valued Pettis integrable function on [0,1] whose primitive is nowhere weakly differentiable. Using their technique and some new ideas we show that ND, the set of strongly measurable Pettis integrable functions with nowhere weakly differentiable primitives, is lineable, i.e., there is an infinite dimensional vector space whose nonzero vectors belong to ND. Introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There are in the literature a number of results related to the topic we are concerned with, see for instance [9,21]. Unless otherwise stated, the measure considered on an interval of R will be always the Lebesgue measure m.…”
Section: Statement Of the Resultsmentioning
confidence: 99%
“…There are in the literature a number of results related to the topic we are concerned with, see for instance [9,21]. Unless otherwise stated, the measure considered on an interval of R will be always the Lebesgue measure m.…”
Section: Statement Of the Resultsmentioning
confidence: 99%
“…We note that Equality (10) follows from the fact that c([σ] k ) = c([τ ] k ) whenever σ ∼ k τ . Equality (11) follows from the definitions of c([σ] k ) and A(n, k). Hence we have just shown that for 1 ≤ k ≤ j, we have…”
Section: Resultsmentioning
confidence: 99%
“…For example, the set of nowhere differentiable functions is lineable [18]. For other examples and survey on the subject refer to [11] [13]. Clearly, the set of chaotic operators cannot be lineable as no operator with norm less than one is hypercyclic.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in the case of a separable Banach space, a linear operator is hypercyclic if and only if it is transitive. The notion of chaos in the sense of Devaney [14] also applies in the setting of Banach spaces. We say that a bounded linear operator T : X → X is chaotic in the sense of Devaney if T is transitive and the set of periodic points of T is dense in X.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the set of nowhere differentiable functions is lineable [19]. For other examples and survey on the subject refer to [8,9,13,15]. Clearly, the set of chaotic operators cannot be lineable as no operator with norm less than one is hypercyclic.…”
Section: Introductionmentioning
confidence: 99%